Exploring STEM postsecondary instructors' accounts of instructional planning and revisions - Robert Erdmann; Kathryn Miller; Marilyne Stains (SpringerOpen, 2020)
Abstract Background Local and national initiatives to improve the learning experiences of students enrolled in Science, Technology, Engineering, and Mathematics (STEM) courses have been on-going for a couple of decades with a heightened momentum within the last 10 years. However, recent large-scale studies have demonstrated that transmission of information is still the primary mode of instruction in STEM courses across the undergraduate curriculum. The limited impact of instructional change reform efforts can be partly explained by the one-sided focus of educational research on the development of evidence-based instructional practices and production of evidence demonstrating their impact on student learning. This has been done at the expense of understanding faculty members' instructional practices and mindsets about teaching and learning that underlie their practices. This study addresses this gap in the literature by characterizing STEM instructors' instructional intentions and reflections on their teaching performance for a week of instruction. Data was collected through semi-structured interviews with 42 STEM faculty members from one doctorate-granting institution in the USA. Results STEM instructors in this study had teacher-centric mindsets with respect to their instructional planning (e.g., content-focused learning goals, lecture is seen as an engagement strategy). We found that these instructors mostly saw formative assessment tools as engagement strategy rather than tools to monitor student learning. Reflections on their level of satisfaction with their week of teaching focused heavily on content coverage and personal feelings and minimally considered student learning. Finally, we found that pedagogical discontent was not a driver of planned course revisions. Conclusions This study identifies mismatches between STEM instructors' teaching mindsets and current approaches to instructional change. STEM instructors in this study paid minimal attention to student learning when considering course-level revisions and many of their reflections were anchored in their personal feelings. However, instructional reform strategies often attempt to convince faculty of a new approach by demonstrating its impact on student learning. The misalignment identified in this study further highlights the need to better characterize STEM instructors' cognition around teaching so that reform efforts can better meet them where they are.